Marketing: a new strategy for state universities in Zimbabwe - Nkala, Doreen; Mugwati, Miriam; Mudzurandende, Florence; Mazhindu, Kenneth; Mhere, Francis (North American Business Press, 2018)
The study explores strategies universities in Zimbabwe are implementing to wade off competition. There are currently fourteen universities, excluding non-university institutions. With stiff competition, institutions’ survival is reliant on enrolments. This paper discusses universities’ marketing strategies to attract and retain both students and staff. Through the RATER Model the research rates service quality in four selected universities. Findings reveal that competency of staff, efficient service delivery, accommodation, and availability of staff to assist students, all enhance rating of university’s service quality. The study recommends continuous monitoring and improvement of service quality in a bid to make for competitiveness.